Greenhouse gas emissions as a result of spectators travelling to football in England - Dosumu, Adekunle (Sci Rep, 2017)
Transport remains a critical avenue in the attempt to reduce greenhouse gas (GHG) emissions and any significant effort to reduce travel GHG emissions will need to encourage a movement towards more fuel-efficient, less polluting behaviours. The aim of this paper is to calculate GHG emissions arising from the travel of spectators to and from football games within eight football tiers (3 to 10) in England, and to extrapolate this to a national level. The study comprised of 1649 participants with an average age of 42 years (M = 42.63, SD = 17.10). Participants travelled to and from games by walking, cycling, car, bus, train or taxi. The average distance travelled to and from games was 41.5 km. A Kruskal-Wallis test was conducted to evaluate differences in travel related GHG emissions between the eight football tiers during the 2012/13 season. The results indicate significant differences between football tiers’ GHG emissions, H(7) = 46.474, p < 0.001. The annual GHG emission of spectators from the 8 tiers for the 2012/13 season was estimated at 56,237 tonnes of CO(2)e, accounting for less than 0.05% of transport emissions in England. Football authorities should have robust travel plans and educate spectators to employ more sustainable travel plans to games.